2013
DOI: 10.1161/str.44.suppl_1.atmp75
|View full text |Cite
|
Sign up to set email alerts
|

Abstract TMP75: Atrial Fibrillation In Ischemic Stroke: Predicting Response To Thrombolysis And Clinical Outcomes

Abstract: Background: Atrial fibrillation (AF) increases the risk of stroke and is associated with poorer stroke outcomes. Few tools are available to evaluate clinical outcomes and response to thrombolysis in stroke patients with AF. Methods: We applied the iScore ( www.sorcan.ca/iscore ), a validated risk score, to consecutive patients with an acute ischemic stroke participating in the RCSN. The main outcome was the proportion of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 0 publications
6
39
0
Order By: Relevance
“…Our measurements for functional status are consistent with most studies, 49 , 50 , 51 , 52 , 53 , 54 , 55 reporting that patients with AF tended to have unfavorable functional outcomes at 90 days before adjustment for any covariates. Consistent with previous studies, 51 , 52 , 53 , 54 our results revealed that the trend of unfavorable outcomes in patients with AF was eliminated after adjustment for the baseline NIHSS scores and other demographic characteristics. By contrast, a recent meta‐analysis in 2021 12 reported that patients with AF had poorer functional outcomes at 90 days and higher SICH rates than patients without AF.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our measurements for functional status are consistent with most studies, 49 , 50 , 51 , 52 , 53 , 54 , 55 reporting that patients with AF tended to have unfavorable functional outcomes at 90 days before adjustment for any covariates. Consistent with previous studies, 51 , 52 , 53 , 54 our results revealed that the trend of unfavorable outcomes in patients with AF was eliminated after adjustment for the baseline NIHSS scores and other demographic characteristics. By contrast, a recent meta‐analysis in 2021 12 reported that patients with AF had poorer functional outcomes at 90 days and higher SICH rates than patients without AF.…”
Section: Discussionsupporting
confidence: 88%
“…First, this study included a larger prospective cohort of patients with and without AF ever treated with IVT than that in previous studies. 49 , 50 , 51 , 52 , 53 , 54 , 55 Second, a solid definition for hemorrhagic transformation was adopted based on NINDS, ECASS II, and SITS‐MOST standards to differentiate between varying severity levels of SICH. Third, by replacing the THRIVE score with the HAT score, SITS‐SICH score, SEDAN score, Cucchiara score, SPAN‐100 Index, and GRASPS score, our study validated the robustness of the primary and secondary objectives.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 However we found no evidence for this, in keeping with larger studies demonstrating no differential effect of thrombolysis on cardioembolic compared to non-cardioembolic strokes. 19,20 Similar to our findings, a recent study found no difference in HU ratio or early recovery depending on whether the aetiology of thrombus was thought to be cardioembolic or atherothrombotic. 9 The significant trend towards reduced parenchymal haemorrhage we observed in patients with HMCAS disappearance is likely due to the smaller ischaemic volume, represented by higher ASPECTS scores and reduced stroke severity.…”
Section: Discussionsupporting
confidence: 91%
“… 24 Saposnik et al included 12,686 patients found that AF patients had a higher risk of death at 30-day, 1-year, and death or disability at discharge more than non-AF patients. 26 A meta-analysis of 8509 patients not only found the same trend as the previous study but also found that AF with stroke increases the risk of ICH due to large infarct size, poor collateral circulation, and large or old thrombi, which lead to IVT resistance, some AF patients may receive the anticoagulant drug before IVT which will increase bleeding risk. 23 Cardioembolism due to AF was recognized as one of the predictors for early parenchymal hemorrhagic transformation, related to unfavorable outcomes following IVT.…”
Section: Discussionsupporting
confidence: 70%